Biomarkers of Nutrition for Development (BOND)—Zinc Review. Issue 4 (9th March 2016) - King, Janet C; Brown, Kenneth H; Gibson, Rosalind S; Krebs, Nancy F; Lowe, Nicola M; Siekmann, Jonathan H; Raiten, Daniel J
Abstract: Zinc is required for multiple metabolic processes as a structural, regulatory, or catalytic ion. Cellular, tissue, and whole-body zinc homeostasis is tightly controlled to sustain metabolic functions over a wide range of zinc intakes, making it difficult to assess zinc insufficiency or excess. The BOND (Biomarkers of Nutrition for Development) Zinc Expert Panel recommends 3 measurements for estimating zinc status: dietary zinc intake, plasma zinc concentration (PZC), and height-for-age of growing infants and children. The amount of dietary zinc potentially available for absorption, which requires an estimate of dietary zinc and phytate, can be used to identify individuals and populations at risk of zinc deficiency. PZCs respond to severe dietary zinc restriction and to zinc supplementation; they also change with shifts in whole-body zinc balance and clinical signs of zinc deficiency. PZC cutoffs are available to identify individuals and populations at risk of zinc deficiency. However, there are limitations in using the PZC to assess zinc status. PZCs respond less to additional zinc provided in food than to a supplement administered between meals, there is considerable interindividual variability in PZCs with changes in dietary zinc, and PZCs are influenced by recent meal consumption, the time of day, inflammation, and certain drugs and hormones. Insufficient data are available on hair, urinary, nail, and blood cell zinc responses to changes in dietary zinc to recommend these biomarkers for assessing zinc status. Of the potential functional indicators of zinc, growth is the only one that is recommended. Because pharmacologic zinc doses are unlikely to enhance growth, a growth response to supplemental zinc is interpreted as indicating pre-existing zinc deficiency. Other functional indicators reviewed but not recommended for assessing zinc nutrition in clinical or field settings because of insufficient information are the activity or amounts of zinc-dependent enzymes and proteins and biomarkers of oxidative stress, inflammation, or DNA damage.